The effectiveness of the ball handling training method on the skills in dribbling basketball for STKIP PGRI Jombang student activity units - Arsika Yunarta; Rahayu Prasetiyo; Novita Nur Synthiawati (International Journal of Basketball Studies, 2023)
The purpose of this study was to determine the effect of ball handling training methods on the dribbling skills of students participating in the basketball student activity unit of STKIP PGRI Jombang. Among these studies are students who follow the Basketball Student Activity Unit of STKIP PGRI Jombang, so 40 students. The sampling technique used in this study was simple random sampling, so that the subjects of this study were students participating in the Basketball Student Activity Unit of STKIP PGRI Jombang, not less than 20 boys and 20 girls. Data analysis techniques are descriptive analysis, normality test and hypothesis testing (paired sample test) using the SPSS program. Based on the results of data analysis, this study concluded that the difference in dribbling ability of extracurricular basketball players at SMA Negeri 5 Soppeng had a significant effect at the time of the pre-test, with an average score of 12.21 seconds. There is a difference between the P-value of 0.000 (P<0.05) and the post-test, where at P-value 0.000 (P<0.05) it reaches an average of 11.20 seconds, a time saving of 1.01 seconds. . Therefore, ball handling training has an impact on the skills of participants in the Basketball Student Activity Unit of STKIP PGRI Jombang. The purpose of this study was to determine the effect of ball handling training methods on the dribbling skills of students participating in the basketball student activity unit of STKIP PGRI Jombang. Among these studies are students who follow the Basketball Student Activity Unit of STKIP PGRI Jombang, so 40 students. The sampling technique used in this study was simple random sampling, so that the subjects of this study were students participating in the Basketball Student Activity Unit of STKIP PGRI Jombang, not less than 20 boys and 20 girls. Data analysis techniques are descriptive analysis, normality test and hypothesis testing (paired sample test) using the SPSS program. Based on the results of data analysis, this study concluded that the difference in dribbling ability of extracurricular basketball players at SMA Negeri 5 Soppeng had a significant effect at the time of the pre-test, with an average score of 12.21 seconds. There is a difference between the P-value of 0.000 (P<0.05) and the post-test, where at P-value 0.000 (P<0.05) it reaches an average of 11.20 seconds, a time saving of 1.01 seconds. . Therefore, ball handling training has an impact on the skills of participants in the Basketball Student Activity Unit of STKIP PGRI Jombang.